Chinese history a new manual = Zhong guo li shi xin shou ce - Wilkinson, Endymion 1941- (Endymion Wilkinson, c/o Harvard University Asia Center, 2018)
"An indispensable guide to the civilization and history of China. Introduces sources from prehistory to the present and examines the context in which the sources were produced, preserved, and received, the problems of research and interpretation associated with them, and the best, most up-to-date secondary works"--
Title in Chinese from front cover
Includes bibliographical references (pages 1023-1119) and indexes
Keywords: Geschichte; China -- History -- Handbooks, manuals, etc; China; Bibliografie; Wörterbuch